Women Enterprise Fund Influence to Women Economic Empowerment Perfomance in Micro F'inance, Case Study, Manyatta Constituency-Embu County - Makuthu, Mulwa J. (University of Embu, 2019)
This study aims on investigating Women enterprise Fund influence to women economic empowerment performance, in Manyatta constituency of Embu County. This research study is guided by the following listed objectives: establishing the extent to which women have benefited from the funds, to establish the challenges faced by women in funds accessibility and to investigate women enterprise fund awareness. ' Kenyan government has provided women funds (WEF) with the principal objective of economic empowerment for meaningful contribution' to national development. Access of this funds will enable women enhance their entrepreneurial skills which will empower them and in turn lead to increase in disposable income through engagement in various types of business. This research study uses a survey research design with a targeted population of over 266 registered women groups in Manyatta constituency at Embu county, out of which a sample of 10 self-help groups were used for the research study. Questionnaires were be administered to selected women self- help groups through simple random sampling procedure for primary data collection. Data was analyzed using descriptive statistics method of analysis with the aid of statistical package for social sciences (SPSS)version 23, and data presentation was through use of tables and pie charts in percentage form.